Patterns of use, knowledge, and perceived effects of sedating medication on driving: A questionnaire survey of Japanese drivers who use sedating medication. (April 2018) - Okamura, Kazuko; Fujita, Goro; Kihira, Makoto; Kosuge, Ritsu
Highlights: Few studies have investigated psychological aspects of drivers using medication. Questionnaire survey on sedating medication use and subjective impact on driving. Medication use is diverse and poly-medication is prevalent. Insufficient awareness/knowledge about potentially impairing effects of medication. A positive association between the number of sedating agents in the medication taken and the self-reported crash involvement. Abstract: Objective: This study was designed to investigate patterns of medication use among drivers using pharmaceutical drugs, the subjective impact of medication use on driving, and knowledge about the effects of medication use on driving. Methods: An online survey was administered to a sample of Japanese drivers (n = 1424, age range 21–79 years) to investigate the use pattern of major sedating medications such as cold/sinus drugs, anxiolytics, hypnotics, and antidepressants. The strength of association between variables pertaining to the use of sedating medications and self-reported at-fault crash involvement was explored using a series of multivariate logistic regression models. Results: On average, respondents reported using 2.7 sedating medications over the past two years (standard deviation = 1.8; range = 0–11). The pattern of psychotropic medication use was diverse, and the use of multiple psychotropic medications was common. Respondents could be grouped into four subgroups in terms of multiple medication use. Irrespective of the type of medication taken, respondents noticed few adverse side effects of medication on driving and generally did not adhere to driving-related product warnings; some respondents were unaware of important facts such as the exacerbation of the effects of medication effects when combining medications. Multivariate logistic regression analyses showed that the presence of a higher number of sedating agents in the medication taken was positively associated with reporting an at-fault crash in the last two years, having longer driving distance, being a commercial driver, receiving more traffic tickets, and having a higher tendency for rules violations. Conclusions: The present study showed that medication use by drivers is diverse and complex, that most drivers are not sufficiently informed of the potentially impairing effects of medication, and that poly-medication use appeared prevalent among those who use psychotropic medications. In line with previous studies, the current study reveals a need for better communication between health experts and patients and for education of all stakeholders. The results also highlighted the need for systematic investigation into cause of crash in light of potential contribution of sedating medication used by the driver, given the low autopsy rate for fatally injured drivers in Japan.